A case of small cell neuroendocrine carcinoma of the ampulla of Vater - Hiroharu Ito; Yoshiyuki Wada; Yuko Takami; Tomoki Ryu; Hiroki Ureshino; Hajime Imamura; Shin Sasaki; Akihisa Ohno; Masayuki Hijioka; Toyoma Kaku; Ken Kawabe; Shigeto Kawauchi; et al. (Surgical Case Reports)
Abstract Background Gastroenteric neuroendocrine carcinomas (NECs) account for 6.2% of gastroenteric neuroendocrine tumors (NETs), and only 1% or less of gastroenteric NETs occur in the ampulla of Vater (AoV). Clinical features of NEC of the AoV remain obscure. Case presentation A 65-year-old man visited a general practitioner because of jaundice, and an abdominal contrast-enhanced computed tomography scan revealed a tumor of 11 mm in diameter, which was enhanced in the arterial phase at the duodenal papilla, with dilation of the upstream bile duct. Gastrointestinal scope revealed an unexposed tumor of the AoV. Based on a biopsy of the site, a moderately differentiated tubular adenocarcinoma was suspected, and pancreatoduodenectomy was performed. Histopathological examination revealed dysplasia and highly proliferative small tumor cells, with solid and nodular formation at the AoV. Histological analysis showed a high mitotic count, and immunohistochemical staining revealed a Ki-67 index of 40–50% and cells positive for synaptophysin, chromogranin A, and p53. Small cell-type NEC was finally diagnosed. Four months post pancreatoduodenectomy, multiple liver metastases developed, and systemic chemotherapy was administered. Salvage liver resection for liver metastases was performed 14 months after the pancreatoduodenectomy. Unfortunately, multiple liver metastases developed 2 months after liver resection, and the patient died 18 months after the pancreatoduodenectomy. Conclusions Neuroendocrine carcinoma originating from the bile duct is very rare; therefore, in this article, we provide a review of the literature and a case report.